Swot Overview of The Implementation of Outpatient Electronic Medical Records at Bhayangkara Hospital Bengkulu - Syaputra, Reka Dwi; Utami Sari, Emi Yela; Khairunnisyah, Khairunnisyah (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The development of information technology in the healthcare sector has encouraged hospitals to adopt Electronic Medical Records (EMR) as an effort to improve the quality, efficiency, and effectiveness of services. However, the implementation of EMR still faces obstacles such as limited infrastructure, suboptimal data completeness, and human resource readiness. This study aims to describe the implementation of EMR in outpatient care at Bhayangkara Hospital Bengkulu using a SWOT analysis, including identifying strengths, weaknesses, opportunities, and threats. The study used a qualitative descriptive design with observations, interviews, and questionnaires with 13 respondents consisting of medical records staff, IT, nurses, and registration. Data were analyzed univariately and then mapped into SWOT categories. The study shows that the main strengths of EMR are the competence of structured medical records staff and the implementation of the system in various service units. Weaknesses include suboptimal technology infrastructure and inconsistent document completeness. Development opportunities lie in government regulatory support, technological advances, and opportunities to increase human resource capacity. Threats include data security risks, regulatory changes, and resistance of some medical personnel to the new system. Strengthening of IT infrastructure, the development of more comprehensive SOPs, and improving human resource competency through continuous training are needed. With the right strategy, RME can be optimized to support service quality and increase hospital competitiveness.